Unexpected new lizard from the Late Cretaceous of southern South America sheds light on Gondwanan squamate diversity - Martinelli, Agustín Guillermo (2021)
The record of Cretaceous terrestrial lizards (Squamata) in South America is patchy, with seven species described from north-eastern and south-eastern Brazil, and few isolated records of iguanians and scincomorphans from the Argentinian Patagonia. Herein we describe a new genus and species of Cretaceous lizard, Paleochelco occultato gen. et sp. nov., based on a partial skull (MACN-Pv-N 120) discovered about three decades ago that was unnoticed in the Colección Paleovertebrados of the Museo Argentino de Ciencias Naturales ?Bernardino Rivadavia?. It comes from rocks of the Upper Cretaceous Bajo de la Carpa Formation (Neuquén Group) exposed at the Campus of the Universidad Nacional del Comahue, north of Neuquén City (Neuquén Province). The new taxon was included into a broad phylogenetic dataset of squamates and it was recovered around the base of Polyglyphanodontia in a constrained analysis using a total-evidence backbone. By contrast, the same, but topologically unconstrained analysis found Paleochelco occultato also around the base of Polyglyphanodontia but alternatively as the sister taxon to Polyglyphanodontia + Scleroglossa or as one of the sister taxa to the Mosasauria + Scleroglossa clade. The new finding, as well as other records from Argentina and Brazil, highlights a complex, still unrecovered, evolutionary history for lizards in the Mesozoic of South America.